Factors Influencing The Usage Of Technology In The Retail Sector In Melaka - Chon, Chieiu Leng (2000)
This paper studies the extend of technology adoption of four big retail businesses in Melaka which consist of food, clothing, hardware and consumer electronics firms. It identifies organisational, structural and strategic factors that characterise small retailers making greater use of technologies.